Comparative Study of Facilities and Practices of Open and Distance Learning Directorates Working in Conventional Universities in Islamabad Capital Territory - Muhammad Ajmal (International Islamic University Islamabad, 2018)
Higher Education Commission in Pakistan permitted to fourteen formal Universities to establish Open and Distance Learning Directorates to run programs through open distance Learning.The main objectives of this study were to find out the available facilities, explore the prevailing practices and to find out the differences in prevailing practices of Open and Distance Learning Directorates working in three conventional universities in Islamabad capital Territory. Directorate of Distance Education International Islamic University, Directorate of Distance Education Comsat Institute of Information Technology, Directorate of Distance Education Sarhad University of Science and Information Technology, Islamabad Campus were selected to conduct the study. The study was descriptive in nature adopting survey design .A Check list, an interview protocol and Questionnaire were used as instruments to check the facilities and practices of ODL Directorates. 539 students, 30 faculty members and three Heads/ Directors were surveyed. The results of the study indicated that these directorates may have sufficient room for improvement in hiring faculty, infrastructure, curricula and facilities needed for ODL system. There was no harmony in the practices of ODL Directorates regarding their course content, content delivery and exam mechanism. It is recommended to provide proper infrastructure and faculty training to run the ODL programs in these directorates. A mutual collaboration mechanism among these directorates should be established for faculty exchange, ICT usage, curriculum Development instructional designing and research projects.